Constructing artificial solid electrolyte interphase by facile chemical reaction for stable lithium metal anodes. (20th November 2022) - Zou, Chao; Zhang, Xingwei; Huang, Yun; Zhao, Ling; Ren, Wenhao; Zhao, Zhixing; Liu, Jiapin; Li, Xing; Wang, Mingshan; Guo, Bingshu; Lin, Yuanhua
Highlights: The construction of the artificial SEI layer is realized by a common solvent DMSO. The components of Li2 SO4 and sulfur-containing organic compounds in SEI are helpful to stabilize the lithium anode. A facile strategy to construct artificial SEI through chemical reaction for lithium metal batteries is proposed. Abstract: Lithium metal is considered one of the most promising anode materials because of its high theoretical capacity and the lowest electrode potential, but practical application is hampered by high reactivity and volume variation in circulation. As a key component, the artificial solid electrolyte interphase (SEI) is designed to effectively stabilize the lithium anode. Here, the chemical reaction between dimethyl sulfoxide (DMSO) and lithium is accelerated in the presence of potassium hydroxide (KOH). The sulfur-containing organic compounds, lithium sulfate (Li2 SO4 ), lithium hydroxide (LiOH) and other favorable components are introduced into SEI, which enable the modified lithium metal anode to have lower interfacial impedance, higher lithium ion transference number, and more uniform Li-ion deposition. The assembled Li-Li symmetric battery realizes a stable cycle of more than 800 h at a current density of 0.5 mA cm −1 and an areal capacity density of 1 mAh cm −1 . The full cell coupled with LiNi0.6 Co0.2 Mn0.2 O2 (NCM622) still maintains 113 mAh g −1 discharge capacity with 63% capacity retention rate after 400 cycles at a current density of 0.5 C. The simple construction of artificial SEI strategy of this study provides an effective strategy for LMBs with superior electrochemical performance. Graphical abstract: Image, graphical abstract